Aspek Hukum Persaingan Usaha dalam Melindungi UMKM Bidang Konveksi dari Praktik Predatory Pricing di Kabupaten Sumedang Perspektif Kaidah Siyasah Al-Ighraq - Nugraha, Alfan Azri; Fautanu, Idzam; Prasetyo, Ridwan Eko (STAIN MAJENE, 2025)
This study employs an empirical juridical approach by analyzing the impact of predatory pricing of Chinese textile imports via TikTok Shop and Shopee on 2,370 garment-convection MSMEs in Sumedang Regency. The findings indicate that garment MSMEs in Sumedang have been significantly affected by predatory pricing, experiencing an 80% decline in production, a 60–70% decrease in turnover, millions of meters of fabric remaining unsold, and the mass layoff of more than 700 employees at PT Wiska. The study also identifies obstacles faced by the Business Competition Supervisory Commission (KPPU) in addressing this issue, including difficulties in proving algorithmic intent, the inadequacy of Law No. 5 of 1999 in accommodating digital market practices, and limited institutional resources. Furthermore, from the perspective of Siyasah al-Ighraq in Islamic economic law, such practices are equated with deliberate dhirar (harm), which violates the legal maxim lā ḍarar wa lā ḍirār and Qur’an Surah Al-Baqarah verse 188 prohibiting the unlawful consumption of others’ property (akl al-amwāl bil-bāṭil), thereby undermining the public interest (maṣlaḥah) in the protection of wealth (ḥifẓ al-māl).